Data for a novel infrared imager for studies of hydroxyl and oxygen emissions in the mesopause above northern Scandinavia - Dalin, Peter (Swedish Institute of Space Physics, 2024)
Data contain hydroxyl and molecular oxygen emission measurements as well as complementary measurements presented in the paper “A novel infrared imager for studies of hydroxyl and oxygen nightglow emissions in the mesopause above northern Scandinavia” submitted to Atmospheric Measurement Techniques in 2023. The data were obtained with a new infrared imaging system (OH imager) for studies of nightglow emissions coming from hydroxyl (OH) and molecular oxygen (O2) layers in the mesopause region (80–100 km) over Kiruna (Sweden).

File Fig2.xlsx contains data on 6 April 2023 shown in Figure 2 of the paper. The first column lists the time [UT, hours]. Raw intensities [digital numbers] of the atmospheric background, OH P1(2) and P1(4) lines are listed in the second, third and fourth column, respectively.

File Fig3.xlsx contains data on the night 6/7 April 2023 shown in Figure 3 of the paper. The first column lists the time [UT, days]. The second column lists the dark-current noise [digital number].

File Fig4.xlsx contains OH(3-1) rotational temperature measurements made on the night 2/3 February 2023 shown in Figure 4 of the paper. The date and time (UT) are shown from the first to sixth column. The OH (3-1) rotational temperature [K] above Esrange is presented in the seventh column.

File Fig5.xlsx contains OH(3-1) rotational temperature measurements shown in Figure 5 of the paper. The first column contains Day of Year 2023. The OH (3-1) temperature [K] above Kiruna and its standard deviation [K] are listed in the second and third column, respectively.

File Fig6.nc is a NETCDF4 format file (https://www.unidata.ucar.edu/software/netcdf/). It contains maps around Kiruna of airglow emission intensities and temperature obtained by the OH imager on 16 February 2023. Intensities of the OH (3-1) P1(2) and P1(4) lines are given in the Rayleigh. Intensity of the O2 IR A-band at 1268.7 nm is given in a relative unit. The OH (3-1) rotational temperature at around 87 km altitude is in Kelvin. A detailed description of all the parameters is given in the metadata to Fig6.nc. The file can be read in Matlab, Python or other scientific software.

File Fig7.xlsx contains OH(3-1) rotational temperature measurements shown in Figure 7 of the paper. The first column contains Day of Year 2023. Daily mean OH (3-1) temperature above Kiruna and its standard deviation are listed in the second and third column, respectively.

File OH_imager_video_160223.avi contains a video sequence of the intensities and temperature maps on 16 February 2023 shown in Fig.6 of the present paper. The video demonstrates a motion of atmospheric gravity waves of various scales, preferentially moving from the south-west to the north-east.

Data innehåller mätningar av hydroxyl- och molekylärt syre-emissioner samt kompletterande mätningar som presenteras i artikeln "A novel infrared imager for studies of hydroxyl and oxygen nightglow emissions in the mesopause above northern Scandinavia" inlämnad till Atmospheric Measurement Techniques 2023. Uppgifterna erhölls med ett nytt infraröttavbildande instrument (OH imager) för studier av nattemissioner som kommer från hydroxyl- och molekylärt syre-lagren (OH och O2) i mesopausregionen (80–100 km) över Kiruna (Sverige).

Filen Fig2.xlsx innehåller data den 6 april 2023 som visas i Figur 2 i artikeln. Den första kolumnen visar tiden [UT, timmar]. Råintensiteter [digitala tal] för den atmosfäriska bakgrunden, OH P1(2)- och P1(4)-linjerna listas i den andra, tredje respektive fjärde kolumnen.

Filen Fig3.xlsx innehåller data om natten den 6/7 april 2023 som visas i Figur 3 i artikeln. Den första kolumnen visar tiden [UT, dagar]. Den andra kolumnen listar mörkströmsbruset [digitala tal].

Filen Fig4.xlsx innehåller OH(3-1) rotationstemperaturmätningar utförda natten 2/3 februari 2023 som visas i Figur 4 i artikeln. Datum och tid (UT) visas från den första till den sjätte kolumnen. OH (3-1) rotationstemperaturen [K] ovanför Esrange presenteras i den sjunde kolumnen.

Filen Fig5.xlsx innehåller OH(3-1) rotationstemperaturmätningar som visas i Figur 5 i artikeln. Den första kolumnen innehåller dagen på året 2023. OH (3-1) temperaturen [K] över Kiruna och dess standardavvikelse [K] anges i den andra respektive tredje kolumnen.

Filen Fig6.nc är en fil i NETCDF4-format (https://www.unidata.ucar.edu/software/netcdf/). Den innehåller kartor runt Kiruna över luftglödemissionsintensiteter och temperatur erhållen av OH-avbildaren den 16 februari 2023. Intensiteter för OH (3-1) P1(2) och P1(4)-linjerna anges i Rayleigh. Intensiteten för O2 IR A-bandet vid 1268,7 nm ges i en relativ enhet. OH (3-1) rotationstemperatur på cirka 87 km höjd är i Kelvin. En detaljerad beskrivning av alla parametrar ges i metadata till Fig6.nc. Filen kan läsas i Matlab, Python eller andra vetenskapliga mjukvara.

Filen Fig7.xlsx innehåller OH(3-1) rotationstemperaturmätningar som visas i Figur 7 i artikeln. Den första kolumnen innehåller dagen på året 2023. Dagsmedelvärde OH (3-1) temperatur över Kiruna och dess standardavvikelse anges i den andra respektive tredje kolumnen.

Filen OH_imager_video_160223.avi innehåller en videosekvens av intensitets- och temperaturkartorna den 16 februari 2023 som visas i Figur 6 i artikeln. Videon visar en rörelse av atmosfäriska gravitationsvågor av olika skalor som företrädesvis rör sig från sydväst till nordost.
Data för en ny infraröd avbildare för studier av hydroxyl- och syreemissioner i mesopausen ovanför norra Skandinavien
Keywords: atmospheric physics; atmosfärfysik; atmosphere; atmosfär; atmospheric physics; Atmospheric conditions; Atmosfäriska förhållanden; mesopause; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Geoscientific Information; Geovetenskap